Phenology of two syntopic Eukoenenia species in a northern Italian forest soil (Arachnida: Palpigradi) - Christian, Erhard; Capurro, Matteo; Galli, Loris (REVUE SUISSE DE ZOOLOGIE, 2010)
Phenology of two syntopic Eukoenenia species in a northern Italianforest soil (Arachnida: Palpigradi). - The present paper provides evidence for the co-occurrence of edaphic palpigrade species in Europe. Eukoenenia mirabilis and E. gallii coexist in the soil of a cork oak plantation on the Ligurian coast in northwestern Italy. Year-round sampling there produced, for the first time in a temperate zone, complete annual cycles of palpigrade populations. In the study area E. mirabilis and E. gallii are univoltine. Both species reproduce in summer and overwinter predominantly in the adult stage. The balanced sex-ratio of the resident E. mirabilis population is remarkable, because males of this widespread species are usually rare or absent.
The following values have no corresponding Zotero field: pub-location: CASE POSTALE 6434, ATTN:DENISE MAIER ADMN REV SUISSE DE ZOOLOGIE, CH-L211 GENEVA 6, SWITZERLAND publisher: MUSEUM HISTOIRE NATURELLE
Keywords: Palpigrades; edaphic; life cycle; sex ratio; Roman

A new soil-dwelling palpigrade species from Northern Italy (Palpigradi: Eukoeneniidae) - Christian, Erhard (ZOOTAXA, 2009)
Among the 27 palpigrade species recorded in Europe so far, 23 occur in caves or narrow subterranean voids. Eukoenenia gallii n. sp. from a cork oak forest on the Italian Riviera (Liguria) is added to the small group of edaphic European palpigrades. E. gallii is not closely related to the common soil-dweller E. mirabilis (Grassi & Calandruccio, 1885), but to E. subangusta (Silvestri, 1903). Body shape and proportions make the new species look extremely edaphomorphic. All instars are described and illustrated with light micrographs of diagnostic traits.
Keywords: Arachnida; diagnostic characters; edaphomorphic; Eukoenenia; EUROPE; Liguria; taxonomy